Application of Ovarian Cancer Organoids in Precision Medicine: Key Challenges and Current Opportunities - Yang, Jiani; Huang, Shan; Cheng, Shanshan; Jin, Yue; Zhang, Nan; Wang, Yu (Frontiers in Cell and Developmental Biology, 2021)
Ovarian cancer (OC) is the leading cause of death among gynecologic malignances. Over past decades, human-derived models have advanced from monolayer cell cultures to three-dimensional (3D) organoids that could faithfully recapitulate biological characteristics and tumor heterogeneity of primary tissues. As a complement of previous studies based on cell lines or xenografts, organoids provide a 3D platform for mutation-carcinogenesis modeling, high-throughput drug screening, genetic engineering, and bio-banking, which might fulfill the gap between basic research and clinical practice. Stepwise, cutting-edge bioengineering techniques of organoid-on-a-chip and 3D-bioprinting might converge current challenges and contribute to personalized therapy. We comprehensively reviewed advantages, challenges, and translational potential of OC organoids. Undeniably, organoids represent an excellent near-physiological platform for OC, paving the way for precision medicine implementation. Future efforts will doubtlessly bring this innovative technique from bench to bedside.